2019
DOI: 10.1177/1836939119841459
|View full text |Cite
|
Sign up to set email alerts
|

What digital technology do early childhood educators use and what digital resources do they seek?

Abstract: Continuing professional learning is vital to early childhood professionals, and the use of digital technology can potentially reduce costs and improve access. In this study, 74 educators across 17 early childhood services in Australian urban and regional locations completed a questionnaire about their personal and professional uses of digital technology to find resources. The results indicate most early childhood educators use digital technology to construct their own professional knowledge bases, and though t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…Teachers and ECEs are currently using this to their advantage through the development of photo and video sharing sites as well as interactive classroom blogs (Parnell & Bartlett, 2012). A recent study conducted in Australia highlighted the growing use of digital technology for observations, reporting, and parent communication, with 14 of the 17 centres (82%) involved in the study using commercially available software for communicating with parents and 96% of the 74 ECEs reporting that they owned a smartphone (Dwyer, Jones, & Rosas, 2019). Digital applications in the classroom enable educators to document children's learning experiences in real time, sending information to parents directly as it happens.…”
Section: The Digital Generationmentioning
confidence: 99%
“…Teachers and ECEs are currently using this to their advantage through the development of photo and video sharing sites as well as interactive classroom blogs (Parnell & Bartlett, 2012). A recent study conducted in Australia highlighted the growing use of digital technology for observations, reporting, and parent communication, with 14 of the 17 centres (82%) involved in the study using commercially available software for communicating with parents and 96% of the 74 ECEs reporting that they owned a smartphone (Dwyer, Jones, & Rosas, 2019). Digital applications in the classroom enable educators to document children's learning experiences in real time, sending information to parents directly as it happens.…”
Section: The Digital Generationmentioning
confidence: 99%
“…There seemed to be an abundance of many smaller resources on the Internet, such as blogs and Facebook groups, and not a central, comprehensive source for music during early childhood library programming. This approach to gathering resources is similar to that described by Dwyer, et al (2019) in their survey study with Australian early childhood teachers. They found that teachers listed informal resources such as Pinterest and Facebook groups as primary resources when seeking materials for the early childhood classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Technology tools, such as digital cameras, digital audio devices, scanners and electronic portfolios, can support educators to systematically monitor and document children’s progress, providing permanent records of children’s work (Hooker, 2015 ; Lyons & Tredwell, 2015 ). A variety of commercial web-based software are available to support the process of planning and documentation (Dwyer et al, 2019 ). Previous research suggests that educators are increasingly adopting such digital resources for the purpose of planning and documentation as it allows ECEC settings to streamline this process (Beaumont-Bates, 2017 ; da Silva & da Silva, 2018 ).…”
Section: Digital Technologies In Early Childhood Education and Carementioning
confidence: 99%
“…These partnerships are essential to develop strong relationships with children due to the vital role families play in their children’s education and care (Fan & Yost, 2019 ; Stamopoulos, 2018 ). ECEC settings commonly use digital technology to facilitate communication between educators and families, encouraging family participation in their children’s education (Beaumont-Bates, 2017 ; da Silva & da Silva, 2018 ; Dwyer et al, 2019 ). Commercial software provides a variety of ways to communicate with families, including learning story templates, conversations, video and audio (Beaumont-Bates, 2017 ).…”
Section: Digital Technologies and Relationships With Families And Com...mentioning
confidence: 99%
See 1 more Smart Citation